A high-altitude peatland record of environmental changes in the NW Argentine Andes (24° S) over the last 2100 years - Schittek, Karsten; Kock, Sebastian T.; Lücke, Andreas; Hense, Jonathan; Ohlendorf, Christian; Kulemeyer, Julio J.; Lupo, Liliana C.; Schäbitz, Frank (Climate of the past, 2016)
High-altitude cushion peatlands are versatile archives for high-resolution palaeoenvironmental studies, due to their high accumulation rates, range of proxies, and sensitivity to climatic and/or human-induced changes. Especially within the Central Andes, the knowledge about climate conditions during the Holocene is limited. In this study, we present the environmental and climatic history for the last 2100 years of Cerro Tuzgle peatland (CTP), located in the dry Puna of NW Argentina, based on a multi-proxy approach.